Effect of Filler Treatment on the Release Properties of Coating on Urea Granules. Issue 1 (2nd January 2019) - Li, Lixia; Cao, Bing; Sun, Yumeng; Yi, Wenping; Ni, Xiaohui; Xiao, Qiang
ABSTRACT: Polyurethane composite coatings on urea granules were prepared by SBA-15 mesoporous silica (in as-synthesized and calcined forms) as a pseudo-crosslinker without any other chain extenders. The calcination of mesoporous silica leaded to reduction of hydroxyl groups and increase of mesopores. The composite coating containing calcined SBA-15 showed enhanced controlled release properties compared with the other two coatings. At the loading content of 1 wt%, the initial release rate and release duration of urea coated by polyurethane/calcined SBA-15 composite were 0.08% and 83 d, respectively. It is shown that the calcination played an important role in controlling the properties of composite coating. GRAPHICAL ABSTRACT: